Describing framework static structure : promoting interfaces with UML annotations - Lopes, Sérgio F. (2006)
Frameworks are an important form of reuse that can help to significantly decrease the time and cost of application development. Although widely known, there are still some difficulties associated with framework reuse, which are critical to its success. In this paper, we focus on the issues regarding the framework reuse process, and more specifically, on the framework architecture description. This paper discusses our position on the subject. It enables a component-oriented approach to framework reuse by emphasizing the description of black-box variation-points, and introducing call-points. We define the UML-FD profile for UML 2.0, which extends UML to support these and other concepts, dedicated to describe the static structure of application frameworks.